The Association of Dry Eye Symptoms with Socioeconomic Factors and quality of Life - Sharon Yeo; Han Tun Aung; Louis Tong (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2014)
Purpose: Dry eye is a common condition with significant morbidity and socioeconomic burden. The associated demographic factors that worsen utility in dry eye patients were not known. There were many questionnaire instruments advocated for dry eye documentation but none of these have been shown to correlate to quality of life (QoL). We aimed at examining the health related utility values in a group of dry eye patients and their associations. Methods: This was a hospital based prospective cross-sectional study conducted at the dry eye clinic of Singapore National Eye Centre. Patients with dry eye symptoms were randomized to one of the two validated symptom questionnaires, Standard Patient Evaluation of Eye Dryness (SPEED) or Symptom Assessment in Dry Eye (SANDE) questionnaires. All patients underwent an evaluation of socio economic factors and utility was assessed using Time-Trade-Off methodby 4 trained interviewers. Results: We recruited 178 participants with dry eye symptoms (mean age was 56.4 (SD: 14.1) years, 77% female), 85 were assessed with SPEED and 93 with SANDE. The utility values encountered were skewed with only 52% of patients having a reduced utility (median=1.0) with a mean of 0.984 (SD: 0.11). The mean SPEED was 11.7 (5.6), and the mean SANDE was 56.8 (22.6). A higher symptom score was associated with a utility less than 1 with odds ratio 2.75 (95%CI 1.50-5.04). The correlation between SANDE and utility was r=-0.295 (-0.47 to -0.097) and corresponding correlation for SPEED and utility was not significant. To detect a utility less than 1, SPEED had an area under the curve (AUC) of 0.63 (95%CI 0.51-0.75) and the SANDE, 0.67 (0.56-0.77). Conclusions: The health related QoL was relatively good in people with dry eye symptoms in this study. Increased symptoms were associated with decreasing QoL but the association was in general weak. This implied that causes of reduced QoL apart from symptoms, such as costs, treatment inconvenience or adverse effects should be explored.